LONG TERM MUCOLYTIC THERAPY WITH DORNASE ALFA AT NOVOSIBIRSK CENTER FOR DIAGNOSTICS, TREATMENT, RHEABILITATION AND ADAPTATION OF CHILDREN WITH CYSTIC FIBROSIS - N.I. Romanenko; E.G. Kondiurina; I.V. Sultanova; A.A. L’vov; A.V. Likhanov (Вопросы современной педиатрии, 2006)
The center for diagnostic, treatment, rehabilitation and social adaptation of patients with cystic fibrosis was established in pulmonology department of the children's clinical hospital № 3 of Novosibirsk in 1994. Since 1995 the database of the center has registered 23 patients. the center has carried out an open prospective study of clinical efficacy and safety of dornase alfa (pulmozyme, «F. hoffmannala roche ltd.», basel) in 10 patients with cystic fibrosis. The patients have received mucolytic therapy with dornase alfa for 2 years (2003–2005). They have been administered a daily inhalation of 2.5 ml of the solution (pulmozyme inhalation solution) containing 2.5 of dornaza alfa. The study has shown an improvement of pulmonary function and elevation of oxygen saturation. The number of respiratory infections have dropped by 33%, the administration of intravenous antibiotics has shortened by 25%, the nutrition status has trended towards improvement. regardless of it's high price, dornasa alfa has proven its' benefits in the treatment of cystic fibrosis in patients of any age and disease severity.Key words: dornase alfa, children, cystic fibrosis, treatment.